2023
DOI: 10.1111/jvp.13114
|View full text |Cite
|
Sign up to set email alerts
|

The plasma and tissue kinetics of sulfadiazine and its metabolite in Ictalurus punctatus after oral gavage at two temperatures

Abstract: A plasma and tissue kinetic study of sulfadiazine (SDZ) and its metabolite, N4‐acetyl sulfadiazine (ACT‐SDZ), was characterized in channel catfish (Ictalurus punctatus) following a single oral dose of 50 mg/kg at 18 and 24°C. Samples were collected at predetermined time points and determined by ultra‐performance liquid chromatography. The classical one‐compartmental method was used to estimate the pharmacokinetic parameters. Results showed that the changing of temperature was markedly influential on the kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
1
0
Order By: Relevance
“…For florfenicol, the T 1/2 in the plasma, liver, kidney, and muscle and skin at 10 °C was more than two-fold in the corresponding plasma and tissues at 25 °C after 5-day consecutive oral administration of FF at a dose of 10 mg/kg [ 23 ]. These results demonstrated that warmer temperatures also accelerated the excretion rate of the aquatic drug because fish are heterothermic animals [ 26 , 29 , 30 ]. Their physiological activity was sensitive to temperature, thereby changing the pharmacological parameters of aquatic drugs to shift the WTs in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…For florfenicol, the T 1/2 in the plasma, liver, kidney, and muscle and skin at 10 °C was more than two-fold in the corresponding plasma and tissues at 25 °C after 5-day consecutive oral administration of FF at a dose of 10 mg/kg [ 23 ]. These results demonstrated that warmer temperatures also accelerated the excretion rate of the aquatic drug because fish are heterothermic animals [ 26 , 29 , 30 ]. Their physiological activity was sensitive to temperature, thereby changing the pharmacological parameters of aquatic drugs to shift the WTs in tissues.…”
Section: Discussionmentioning
confidence: 99%
“…When drugs complete their transportation and disposition in a host organism, they can be non-specifically and reversibly bound to plasma and tissue proteins [4]. It is well-accepted that only the free drug, without binding with plasma protein, can oppose pathogens, and it decides the apparent volume of distribution to influence the drug clearance in the liver and in kidney tissues [5][6][7][8]. Therefore, a better understanding of the functions PPBRs in plasma is important for designing rational dosage regimens for drugs in order to promote therapeutic efficiency and avoid treatment failure.…”
Section: Introductionmentioning
confidence: 99%